The Promise of Interreligious Dialogue for a World in Conflict - Fitzgerald, Michael L. (Studies in Christian-Jewish Relations, 2011)
Archbishop Michael L. Fitzgerald, M.Afr. until recently served as the president of the Pontifical Council for Interreligious Dialogue in the Vatican. In February 2006 he was appointed by Pope Bendedict XVI to be the apostolic nuncio to Egypt and the Holy See's delegate to the League of Arab States. This address was delivered at the conference "In Our Time: Interreligious Relations in a Divided World," co-sponsored by the Center for Christian-Jewish Learning at Boston College and Brandeis University to mark the 40th anniversary of Nostra Aetate. It was given at Boston College on March 16, 2006. After reviewing regions of conflict in the world, Archbishop Fitzgerald first discusses what interreligious dialogue cannot do. He then explores the Catholic Church's understanding of dialogue as reflected in Nostra Aetate. He considers how a history of past conflicts can be overcome by (1) forgetting the past; (2) achieving mutual understanding; and (3)collaborating. Finally, he examines how dialogues can be encouraged through good neighborliness, through organized action, with intellectual backing, and with spiritual backing.